STRATEGIC PARTNERSHIP BETWEEN UNIVERSITY AND ENTERPRISES AS THE BASIS OF INNOVATION ECONOMY DEVELOPMENT - Nikolay A. Shevelyov (Moscow Polytechnic University, 2022)
This article discusses forms of interaction between university and enterprises, the models of partnership that enable to ensure the real influence of employers on the quality of specialists' training. Perm National Research Polytechnic University has elaborated the system of mutually beneficial interaction with the leading industrial enterprises in Perm region and in Russia, which includes traineeship for lecturers and university workers, attracting of noted scientists from research centers and institutions, experts from enterprises to learning process, participation of employers in tutorial councils, cofinancing of university projects, organization of students' practical work and others.